31.4k views
1 vote
Please help me out with this

Please help me out with this-example-1
User EWizardII
by
4.9k points

2 Answers

7 votes

Explanation:

(2x-1)(3x+2) = 0

6x + 4x - 3x - 2 = 0

7x - 2 = 0

7x = 2

X = 2/7

Fill in this X for the 2 formulas, I'll do the first one:

2 * 2/7 - 1 =.....

Then take the 2 answers you get and multiply them with each other so you get the surface size (length * width)

User Mike Pala
by
4.4k points
0 votes
(3x+2)(2x-1) , it says only write an expression
6x2+x-2, in case you want it in simpler form
User AlexanderBrevig
by
5.1k points